(3GdefMd ef cJGH EUdGM GdefWbs - (3CHh GdbGSe GdMSf Hf Ydj Hf GdMSf GdeZQHj , (B418 (3g` g`s
(3ChdgG (B:s
(3GdMeO ddg HbOQ fYeJg hEfi deG hLOJ EUdGM GdefWb WQjbkG eYjOkG dSdGc GdCOH hOGQkG eMdGdkG ef QhGO GdYde GdLRA GdChd CeKdI GdCSeGA s
(3BNQgG (B:s
(3hGZGQJ HfObg aCHGQJ hbjd JQNje MOGA hQLY HNai Mfjf QLd COYi Edi CSO Hf gGTe aCJi YHO GdeWdH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GddZIs